Estudio geológico-geotécnico previo a la construcción de la planta de tratamiento de agua potable para la parroquia san pedro de vilcabamba, cantón y provincia de Loja. - Mosquera Romo, José Miguel (2019)
The present investigation denominated "GEOLOGICAL-GEOTECHNICAL STUDY PRIOR TO THE CONSTRUCTION OF THE POTABLE WATER TREATMENT PLANT FOR SAN PEDRO DE VILCABAMBA, CANTON AND PROVINCE OF LOJA", it has as main goal to know the main geotechnical geological characteristics of these lands with the objective of guaranteeing the stability of the construction throughout the useful life of it, in view of the short time that the current treatment plant has lasted, which presents serious damage to a large part of its infrastructure, considering that approximately 2805 inhabitants are beneficiaries of this basic service. This research executes a descriptive methodology; all the activities carried out are detailed step by step, starting with a bibliographic information referring to the general conditions of the location, followed by a field work which involved activities such as topography, photointerpretation, general and detailed geology, structural geology, and an inventory of mass movements. In addition, tests of mechanic of soils, refraction seismic, SPTs and assessment of rock masses were done, based on these, the real geotechnical geological condition of the land under study was determined, it was found the presence of three strata and it was obtained cohesion values of 1.3 kg / cm2, for the elevation of 1933 meters above sea level and 1.42 kg / cm2 for the elevation of 1969 meters above sea level, where the various structures of the water plant will be built. The obtained result in the first SPT, is something to worried about, because it shows the presence of clay of low plasticity, this type of lithology is very sensitive to changes of humidity, and transform the soil from semi-solid to liquid condition when there is water on the ground creating a negative scenario before the construction of such an important building, but also it shows us how careful we must be in the future, considering the water that can enter to the subsoil below the treatment plant. The investigation determines that prior to the application of some corrective measure, the construction of the new potable water treatment plant is feasible in the lands that have been destined for this purpose.